Optimizing wheat blends for customer value creation: a special case of solvent retention capacity - Haas, Nikolas C. (Kansas State University, 2011)
The intent of this thesis is to conduct a case study on the optimization of blending soft red winter wheat, prior to processing into flour, in order to meet specific solvent retention capacity, SRC, specifications, based on predetermined customer specifications. The thesis will provide the company with a greater understanding of how to effectively manage the customer’s demands, and the costs associated with these activities in order to create greater customer value. If optimizing wheat blends is successful, the company will be able to provide similar SRC information to other customers as a value added service. (Solvent retention capacity) is a test that provides analytical data that measures three specific physical components within soft wheat flour. Traditionally, wheat flour is sold according to moisture, ash, protein content, and basic dough characteristic data; though this information is important, SRC provides specific flour functionality information that will aid customers. SRC examines the: glutenin characteristics of the flour, pentosan content and gliadin characteristics, and the starch damage from the milling process. These values describe the functionality of the flour and provide information regarding the flour’s ability to absorb water during the mixing process and the flour’s ability to release that water during the baking process. SRC quality endpoints include: reduced mixing and baking times, reduced levels of breakage after baking, and greater overall ingredient consistency throughout all the customer’s commercial bakeries. This thesis develops a process that the company may use to meet SRC quality specifications determined by the customer. The company gains customer loyalty by supply a consistent product to the customer. This product in turn yields savings for the customer in the areas of lower water use, shorter baking time and consequently lower energy use.
Keywords: Solvent Retention Capacity; Wheat; Flour; Cookies and Crackers; Economics, Agricultural (0503); Economics, Commerce-Business (0505); Food Science (0359)